The succinoglycan riclin restores beta cell function through the regulation of macrophages on Th1 and Th2 differentiation in type 1 diabetic mice. Issue 22 (29th October 2021) - Ding, Zhao; Cheng, Rui; Yang, Yunxia; Zhao, Yang; Ge, Wenhao; Sun, Xiaqing; Xu, Xi; Wang, Shiming; Zhang, Jianfa
Abstract : Schematic illustration of the effect of riclin on macrophage activation and the underlying mechanism of riclin improves diabetes in STZ-induced diabetic mice. Abstract : Bacterial succinoglycan is found suitable as a viscosifying and emulsifying agent in the food industry. Riclin is a de-succinyl succinoglycan from an Agrobacterium isolate. Our previous study has revealed that riclin exerts special anti-inflammatory effects in vitro and in vivo . This study aims to determine the effects of riclin on preventing against immunological injury of beta cells in a type 1 diabetic model. We found that orally riclin effectively restores beta-cell function and improves the complications of streptozotocin (STZ)-induced diabetes. Riclin also reduces STZ-induced liver and kidney damage, and balances the inappropriate ratio of T helper type 1 cell (Th1)/type 2 cell (Th2) in the spleen and pancreatic draining lymph nodes of the STZ-induced diabetic mice. In a co-culture system with the islet β cell MIN6 and macrophage RAW 264.7, riclin reduces the levels of IFN-γ and IL-1β, protecting against STZ-caused MIN6 cell injury. We identified that riclin specifically binds to the membrane of macrophages and regulates the ratio of IL-10 and IL-12, thereby inhibiting the macrophage-mediated polarization of Th1 cells and promoting the differentiation of Th2 cells, which depends on the dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) receptor. Moreover, orally riclin significantly decreases the incidence of STZ-induced hyperglycemia (7.1% in riclin vs. 92.9% in STZ), and prevents autoimmune diabetes in non-obese diabetic (NOD) mice, with 87.5% of mice free of diabetes compared to 46.6% of the control mice. These results suggest that riclin has potential to be a functional food to prevent and improve autoimmune diabetes and related diseases.